2014
DOI: 10.1063/1.4892667
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prostate cancer screening based on serum surface-enhanced Raman spectroscopy and support vector machine

Abstract: This study aims to present a noninvasive prostate cancer screening methods using serum surface-enhanced Raman scattering (SERS) and support vector machine (SVM) techniques through peripheral blood sample. SERS measurements are performed using serum samples from 93 prostate cancer patients and 68 healthy volunteers by silver nanoparticles. Three types of kernel functions including linear, polynomial, and Gaussian radial basis function (RBF) are employed to build SVM diagnostic models for classifying measured SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 17 publications
(25 reference statements)
2
93
1
Order By: Relevance
“…[27][28][29] An investigation into diagnosing PCa in 2015 reported that by analyzing the Raman spectra of serum separated from a peripheral blood sample and applying SVM techniques, PCa could be diagnosed with an accuracy of up to 98.1%. 24 While this study offered extremely promising results, it focused on developing the methodology for using SERS in PCa diagnosis and thus did not study the method in a clinically relevant situation. Thus, this method would become closer to clinical application if it was tested on clinically relevant subjects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29] An investigation into diagnosing PCa in 2015 reported that by analyzing the Raman spectra of serum separated from a peripheral blood sample and applying SVM techniques, PCa could be diagnosed with an accuracy of up to 98.1%. 24 While this study offered extremely promising results, it focused on developing the methodology for using SERS in PCa diagnosis and thus did not study the method in a clinically relevant situation. Thus, this method would become closer to clinical application if it was tested on clinically relevant subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our study, there was another research that also used surface-enhanced Raman spectroscopy (SERS) to measure serum spectra for prostate detection and showed great advantage as an invasive method. 24 This work involved normal and PCa participants with support vector machine (SVM) classification and lack of BPH discrimination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many machine learning algorithms, SVM belongs to the family of kernel-based classifiers, and they are very powerful classifiers, as they can perform both linear and non-linear classification simply by changing the "kernel" function utilized [23]. SVM has been widely used in the realm of EEG [24][25][26][27].…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…PSA detection is the important screening means, but the PSA test can lead to overdiagnosis because PSA levels are low in some subjects with prostate cancer, so the US Preventive Services Task Force does not recommend screening for prostate cancer based on PSA at present. Recently, the surfaceenhanced Raman spectroscopy (SERS) in combination with support vector machine (SVM) has been successfully applied in classification of prostate cancer from normal subjects by detecting peripheral blood [2]. We feel that blood SERS will open a new approach for noninvasive screening prostate cancer at the early stages.…”
mentioning
confidence: 99%